(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Treatment for exudative otitis media (ESM) in most cases requires topical application of medications that are designed to stop the inflammatory process and affect the exudate in the middle ear cavity. One of the most common methods of treating ESOis ear tube catheterization with a Guillot catheter, which is not alwayseffective. This paper presents the second stage of the study on the introduction of drugsinto the middle ear using an original ear catheter. The study included patients with ESO (N = 14, disease duration from 2 to 3 months). Patients underwent surgical treatment: eardrumbypass surgery, septoplasty, and turbinoplasty under endotracheal anesthesia. An intraoperative experiment was conducted to evaluate the effectiveness of ear tube catheterization with an original catheter, tinted solution andMiramistin solution. In all 14 cases, the tympanic membrane of the affected ear performed oscillatory movements during catheterization, in sync with the reciprocating movements of the syringe plunger. In 2 cases (14.3%), we did not visualize the colored solution behind the eardrum. Total fillingof the tympanic cavity with tinted saline solution was 4 patients (28.6%), while the average volumeof the administered solution (V) was 4.09 ml, in 8 ears (57.1%) the tympanic cavity was partially filled with contrast solution (V = 7.0 ml). When transtubary administrationof Miramistin solutioninto the tympanic cavity in all cases (14 ears) – ingress of antiseptic solution into the external auditory canal after miringotomy. Comparing the average volume of the tympanic cavity with the volume of the drug administered, which is necessary for the initial filling of the tympanic cavity, the minimum loss of the liquidform of the drug was 1: 2.